(untitled) (Journal of Health Informatics in Africa, 2020)
Background and Purpose: Electronic health (eHealth) is the use of information and communication technology (ICT) to support healthcare. It is becoming more popular in healthcare management with expectations of improved effectiveness, access, quality, and efficiency of the healthcare systems. The increased investment and implementation of eHealth across the world calls for its evaluation to evidence its value. This study thus aimed at investigating the practices, challenges, and suggestions for optimising the evaluation of eHealth interventions in Uganda. Methods: A cross-sectional survey was used to conduct the investigation among key eHealth implementing institutions in Uganda. Primary data provided by 22 participants from 18 institutions were used to establish an understanding of the institutions’ perspectives with respect to eHealth evaluation practices and challenges faced, as well as to derive insights from these perspectives in relation to the World Health Organization (WHO) understanding of digital health evaluation. Results: The study revealed that various eHealth interventions are implemented in Uganda; however, very little of their evaluation is undertaken, as it is not a key activity with most of the eHealth implementers. Focus is put on monitoring the eHealth initiatives’ functionality and adoption rather than their outcome and impact. Limited skills/capacity and unavailability of national guidelines on eHealth evaluation were reported as key limitations. Conclusions: Accordingly, the study recommends the need for an evaluation framework to elucidate and guide on the notion of evaluation, its characteristics, and measurement indicators regards the outcome and impact of eHealth interventions in healthcare and service delivery for Uganda’s health system.